THE CONCEPT OF TOLERANCE IN ISLAMIC EDUCATION - Ghazali, Adeng Muchtar (Jurnal Pendidikan Islam, 2016)
This article aims to discuss comprehensively the concept of tolerance in Islam later thought in such a way that the concept can be applied operationally in Islamic educational institutions such as madrassas, Islamic boarding schools and colleges. Methods and approaches used to address this issue are philosophical (phenomenological) and the sociology of education, one of which is the theory of inclusivism Mircea Eliade. In Islam, different thoughts, tribes, and even religion (adherents) refer to fitrah and sunnatullÄh of Godâ€Ÿs will. For this reason, then, tasÄmuh (tolerance) becomes an important doctrine in every religion treatise, including in Islamic education system i.e; 1) to have responsive toward modernization which has been existed in general school institutions under Ministry of Education; 2) to develop sensitive character toward the change through apporiate learning strtategy and developing children psycho-social condition, modernizing learning facilities, environment, and other supporting factors including the involevement of parents, government, society and other education stakeholder; 3) to implement a model to strengthen inclusive Islamic education system which is opened, dialogic, and student-centered; 4) to bear a strong and tough human reseource with high tolerance who will act to occupy and create new civilization emphasizing on religion, spritual and humanism values; 5) to develop networking and corporation both national and international to expand informationn access, funding, and other international supports.